Vertical integration, foreign multinationals and Stigler's hypotheses: an empirical test using Malaysian data - Md. Nor, Nor Ghani; Abdullah, Ahmad Zainuddin; Md. Nor, Khalil (East Asian Economic Association and Blackwell Publishing Ltd, 2006)
In this paper the hypotheses on motives for vertical integration as proposed by Stigler are empirically tested using a panel dataset from Malaysian manufacturing under both fixed-effects and random-effects specifications. Because the degree of multinational participation is expected to influence the results of the regression estimates, empirical tests are conducted with and without controlling for the effect of foreign firms' participation. Depending on model specifications, evidence is found in favor of Stigler's hypotheses where vertical integration is positively related to demand growth and industry concentration. This result is generally consistent with those found in other vertical integration studies. Significantly, the coefficient estimates of the growth variable are not significant and biased downwards if there is no control on the effect of foreign multinationals in the estimation process. © 2006 East Asian Economic Association and Blackwell Publishing Ltd.